Meningioma — defining characteristics of the affected Pakistani population - Mashal Murad Shah; Muhammad Usman Khalid; Mohammad Hamza Bajwa; Saqib Kamran Bakhshi; Saad bin Anis; Naveed Zaman Akhunzada; Altaf Ali Laghari; Muhammad Faraz Raghib; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To ascertain the age and gender differences, treatment, and management of meningiomas across Pakistan. Methods: Data were collected as part of the PBTES, and patients with a histopathological diagnosis of an intracranial meningioma in 2019 that presented at these centres were included in this cohort study sub-analysis. Thirty-two centres participated in the study. Medical students, residents, and faculty collated data from medical records. Results: Our data indicate that meningiomas constitute 15.6% of all intracranial tumours in Pakistan and occur more often in females (236, 55%) than in males. The mean age at diagnosis was 43.7 ± 19.9 years. Meningiomas had a slightly higher preponderance in the right hemisphere of the brain at 203 (47.32%) tumours and 267 (62.2%) of the tumours in the frontal and parietal lobes. We found that 174 (61.3%) of all meningiomas diagnosed in Pakistan in 2019 were grade I tumours, which was also the most commonly occurring tumour grade. Adjuvant chemoradiotherapy for meningiomas was rarely observed in Pakistan. Conclusion: The PBTES reveals a low hospital-based incidence of meningiomas in 2019 when compared to the incidence in high-income countries but found evidence similar to those of other LMICs. Tumour characteristics, such as location, grading and surgical procedures, were similar to global literature. Keywords: Meningioma, Chemoradiotherapy, Brain Neoplasms, Epidemiology, Gender traits. Continue...